2017
DOI: 10.1093/humupd/dmx010
|View full text |Cite
|
Sign up to set email alerts
|

Motoring through: the role of kinesin superfamily proteins in female meiosis

Abstract: Kinesin motor proteins have distinct and important roles throughout oocyte meiosis in many non-mammalian model species. However, the functions these proteins have in mammalian meiosis, particularly in humans, are less clear owing to lack of research. This review brings to light the need for more experimental investigation of kinesin motor proteins, particularly those associated with maternal ageing, cryopreservation or exposure to environmental toxicants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 115 publications
0
23
0
Order By: Relevance
“…10 More than 45 kinesins have already been identified in human cells. 11 Kinesins carry out critical functions in the processes of mitosis and cytokinesis. 11 Additionally, previous studies demonstrated that kinesins could promote the separation of sister chromatin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 More than 45 kinesins have already been identified in human cells. 11 Kinesins carry out critical functions in the processes of mitosis and cytokinesis. 11 Additionally, previous studies demonstrated that kinesins could promote the separation of sister chromatin.…”
Section: Introductionmentioning
confidence: 99%
“…11 Kinesins carry out critical functions in the processes of mitosis and cytokinesis. 11 Additionally, previous studies demonstrated that kinesins could promote the separation of sister chromatin. 12 Kinesin family member 4A (KIF4A), a motor protein involved in multiple cellular processes such as spindle formation, chromosome segregation, and cytokinesis.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these kinesins have also been shown to play an essential role in meiosis, mainly during meiosis I, where recombination takes place. [7][8][9]. Kinesin-8 is one class of these motors that is conserved across eukaryotes [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Kinesins bind to cargo via their variable tail regions, and the head (globular motor domain) moves the complex to its destination (Hirokawa, 1998). Many kinesins are involved in regulation of oocyte meiosis (Camlin et al, 2017b). Subito, a member of the kinesin 6 family, participates in spindle organization, stability and bipolarity in Drosophila oocytes (Jang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%